Making Time with Amateur Astronomers and Orbital Space Debris: Attunement and the Matter of Temporality. (30th May 2018) - Reno, Joshua
Abstract : This paper compares the material practice of amateur astronomers with that of archaeologists, specifically arguing that they engage with materials and time in distinct but complementary ways. In particular, the paper outlines the ways in which amateur astronomers become attuned to the temporal cycles and rhythms of extraterrestrial materials as they gaze into the night sky, much like how archaeological practitioners must get to know the taphonomic processes involved in the formation of archaeological sites. Finally, it is argued that for these reasons astronomers might offer insights to the investigation of orbital space debris, a topic of interest among archaeologists of outer space, and materials that produce their own threatening and nested temporalities.